Somewhere in-between: Inner speech and proto-mental content - Destéfano, Mariela Natalia (2023)
In this paper, I explain emerging mental content by focusing on the role of inner speech in reading acquisition. I offer a hybrid explanation that relates a Vygotskian conception of inner speech (constructivism) to dual-route psycholinguistic models of reading (cognitivism) and the notion of content-involving mental states based on socio-cultural practices (enactivism). I first clarify some of the presuppositions that allow for my proposed conception of proto-content. Second, I explore the relationship between inner speech and reading acquisition. Lastly, I develop a notion of “proto-content” grounded in the idea of internal aboutness.